The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3389/ffgc.2021.764357
|View full text |Cite
|
Sign up to set email alerts
|

Getting a Grip on the Adhesion Mechanism of Epiphytic Orchids – Evidence From Histology and Cryo-Scanning Electron Microscopy

Abstract: Plants and animals evolve different attachment structures and strategies for reversible or permanent adhesion to different substrate types. For vascular epiphytes, having the ability to permanently attach to their host plants is essential for establishment and survival. Unlike mistletoe roots, roots of vascular epiphytes do not penetrate the host tissues but instead achieve attachment by growing in close contact to the surface of the substrate. However, the fundamental understanding of the attachment functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Our observation of a glue‐like substance is not the first for epiphytes. It has been described for epiphytic orchids (Tay et al, 2021) and ferns (Testo and Sundue, 2014). Such a substance has also been observed at the root–substrate interface in numerous attachment systems of climbers and seagrasses (e.g., Darwin, 1867; Groot et al, 2003; Melzer et al, 2011; Steinbrecher et al, 2011; Bohn et al, 2015; Zenone et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our observation of a glue‐like substance is not the first for epiphytes. It has been described for epiphytic orchids (Tay et al, 2021) and ferns (Testo and Sundue, 2014). Such a substance has also been observed at the root–substrate interface in numerous attachment systems of climbers and seagrasses (e.g., Darwin, 1867; Groot et al, 2003; Melzer et al, 2011; Steinbrecher et al, 2011; Bohn et al, 2015; Zenone et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The recent study by Tay et al (2021) found that on a relatively smooth bark substrate, the mechanics of attachment for epiphytic orchids occurs at the scale of the root hair–substrate interface where the actual contact area is defined (see fig. 6 of Tay et al, 2021). Therefore, the concept of rugosity in terms of how it is measured and how it relates to epiphyte abundance and richness should be discussed based on how attachment is defined in the first place.…”
mentioning
confidence: 99%
See 3 more Smart Citations